Reinforcement of GFRP Tensile Specimens with Central Holes Using Bonded Composite Patches - Paiva, Fernando E.L.; Reis, João M.L.; Costa Mattos, Heraldo S. da (Journal of Composites and Biodegradable Polymers, 2023)
The use of bonded composite patches is a promising repair/reinforcement method to extend service live of damaged structures. These patches are non-corroding, lightweight, easy to fabricate and have high specific modulus and strength. In this work, the tensile behavior of a patch-reinforced composite specimen with a central hole is analyzed experimentally. A 10-ply composite tensile specimen is prepared by using bidirectional woven e-glass fabric and epoxy resin as the matrix material. The damage is created in the specimen by drilling three different holes with 3, 6 and 10 mm diameter at the center. The specimen is then reinforced by bonding composite patches or carbon steel patches with different lengths as external patches on both external surfaces. Tensile tests have been carried out on the undamaged, damaged, and repaired specimens. From the tensile tests, it was possible to verify the reduction of the strength (measured by the rupture force) of the specimens with holes of 3 mm, 6 mm and 10 mm. The patches were manufactured using the same glass fiber reinforced plastic, GFRP, used in the specimens or carbon steel. The patches were 25,0 mm wide, 2,5 mm thick. The length was 20 mm, 40 mm or 60 mm. It was found that GFRP patches has better efficiency than carbon steel patches. The repairs with GFRP patches were able to restore between 80% and 90% of the mechanical properties of the intact GFRP specimen without the necessity to replace the composite material.